Innovative Islamic Education Learning Media For Internalizing Islamic Perspectives on Technological Developments - Febrianto Sabirin; Umi Liwayanti; Dochi Ramadhani; Dewi Sulistiyarini (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study employed a Research and Development (R&D) approach to create ICT-based interactive learning media for the Islamic Religious Education (PAI) course, integrating game-based and quiz features on the topic of Islamic perspectives on technology. The development followed the ADDIE model, covering analysis, design, development, implementation, and evaluation stages. Validation involved two media experts and two material experts, while limited implementation engaged 30 undergraduate students from the Information Technology Education Study Program. Data were collected through document analysis and questionnaires assessing both feasibility and user responses. The results indicated that the learning media was highly feasible, with scores of 95.83% from media experts and 90.63% from material experts. Student responses also reflected strong acceptance, falling into the very good category with an average score of 83.19%. These findings suggest that the developed media is both effective and user-friendly, providing a valuable tool to enhance PAI learning in higher education. The study demonstrates that integrating ICT, gamification, and interactive features can significantly support students’ engagement and comprehension in religious education, offering a practical model for developing innovative learning resources in tertiary education contexts.